2013
DOI: 10.3892/ijo.2013.1814
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 mitogen-activated protein kinase alters microRNA expression and reverses epithelial-to-mesenchymal transition

Abstract: Acquired chemoresistance and epithelial-to-mesenchymal transition (EMT) are hallmarks of cancer progression and of increasing clinical relevance. We investigated the role of miRNA and p38 mitogen-activated protein kinase (MAPK) signaling in the progression of breast cancer to a drug-resistant and mesenchymal phenotype. We demonstrate that acquired death receptor resistance results in increased hormone-independent tumorigenesis compared to hormone-sensitive parental cells. Utilizing global miRNA gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 83 publications
2
23
0
2
Order By: Relevance
“…The transforming growth factor (TGF)-β/small mothers against decapentaplegic (Smad) and mitogen-activated protein kinase (MAPK)/P38 signaling pathways are involved in promoting EMT and are associated with the development of DN (10,11). The aim of the present study was to determine the role of the MAPK/P38 and TGF-β/Smad signaling pathways in HG-induced EMT, and to examine the changes in the two pathways in HK-2 cells cultured with procyanidin B2.…”
Section: Introductionmentioning
confidence: 99%
“…The transforming growth factor (TGF)-β/small mothers against decapentaplegic (Smad) and mitogen-activated protein kinase (MAPK)/P38 signaling pathways are involved in promoting EMT and are associated with the development of DN (10,11). The aim of the present study was to determine the role of the MAPK/P38 and TGF-β/Smad signaling pathways in HG-induced EMT, and to examine the changes in the two pathways in HK-2 cells cultured with procyanidin B2.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS/p38-MAPK signaling pathway has been reported to be involved in EMT in the different cells [12,13]. Having shown that SiRNA-HMGA2 inhibited EMT, we next explored the effect of SiRNA-HMGA2 on ROS/P38-MAPK signaling pathway in NRK-52E cells.…”
Section: Sirna-hmga2 Inhibit Ros/p38 Pathwaysmentioning
confidence: 99%
“…STAT5, an important signal transducer and transcription activator, has an important role in the Janus kinase/STAT signaling pathway (8). Its expression level has been shown to be significantly increased in tumors, where it is directly involved in differentiation, invasion, proliferation and apoptosis (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%